Une frontière ouverte à tous les vents : la construction de l’identité collective de l’île de Kinmen - Xiyan Wang (In Situ)
Kinmen Island, only about 10 kilometres away from mainland China, is located opposite the city of Xiamen, Fujian Province. After retreating from the mainland in 1949, Chiang Kai-shek fled to Taiwan and made this island a military base where the KMT (the Chinese nationalist party) stationed much of the army with a view to retaking the mainland. Taiwan’s martial law was lifted in 1987 and the de-militarisation of Kinmen has led to a gradual influx of tourists. Visitors come to Kinmen for different reasons. Some people come to appreciate the natural scenery and historic dwellings that have not been affected or damaged by urban expansion, while others come to visit the remaining fortifications and military heritage of the Civil War. Given its crucial border situation, Kinmen has become an ideal field of observation to study Chinese culture and the natural heritage. Through the ethnographic fieldwork on the heritagisation process of Kinmen, the author tries to explain how the widely prevalent concept of ‘the wind of Wen blows strongly’ (Wen Feng Ding Sheng,文风鼎盛, flourishing literature and education) is reflected through the post-war heritage buildings. This expression actually reveals the Kinmen citizens’ strong attachment to their own history and environment. By describing and analysing the architectural and cultural phenomena in this particular border area between mainland China and Taiwan, this article helps us to obtain an in-depth understanding of the concept of ‘literary culture’ (Wen) in Chinese culture, as well as how residents of Kinmen establish and maintain a new post-war collective identity through the wind of Wen.